Child and adolescent psychopathology - Beauchaine, Theodore P. (Wiley)
Developmental psychopathology as a scientific discipline : relevance to behavioral and emotional disorders of childhood and adolescence / Steven P. Hinshaw -- A multiple-levels-of-analysis perspective on research in development and psychopathology / Dante Cicchetti -- Genetic and environmental influences on behavior / Theodore P. Beauchaine, Steven P. Hinshaw, and Lisa Gatzke-Kopp -- Child maltreatment : a neurodevelopmental perspective on the role of trauma and neglect in psychopathology / Bruce D. Perry -- Impulsivity and vulnerability to psychopathology / Theodore P. Beauchaine and Emily Neuhaus -- Behavioral inhibition as a risk factor for psychopathology / Jerome Kagan -- Exposure to teratogenic agents as a risk factor for psychopathology / Susanna L. Fryer, Nicole A. Crocker, and Sarah N. Mattson -- Brain injury as a risk factor for psychopathology / Lisa M. Gatzke-Kopp and Katherine E. Shannon -- Affective style and risk for psychopathology / James A. Coan and John J.B. Allen -- Emotion dysregulation as a risk factor for psychopathology / Pamela M. Cole and Sarah E. Hall -- Attention-deficit/hyperactivity disorder / Joel Nigg and Molly Nikolas -- Oppositional defiant disorder, conduct disorder, and juvenile delinquency / Benjamin B. Lahey -- Antisocial personality development / Kristina D. Hiatt and Thomas J. Dishion -- Prevalence of alcohol and drug involvement during childhood and adolescence / Sandra A. Brown -- Anxiety disorders / Carl Weems and Wendy Silverman -- Depressive disorders / Daniel N. Klein, Dana C. Torpey, and Sara J. Bufferd -- The development of borderline personality disorder and self-injurious behavior / Sheila E. Crowell, Theodore P. Beauchaine, and Mark F. Lenzenweger -- Bipolar disorder / Joseph C. Blader and Gabriella A. Carlson -- Autism spectrum disorders : a developmental perspective / Geraldine Dawson and Susan Faja -- Childhood schizophrenia / Robert F. Asarnow and Claudia L. Kernan -- Eating disorders / Eric Stice and Cynthia M. Bulik